Field Study on Underwater Noise Emitted by Small Tourist Boats. Comparison Between the Use of Electric and Combustion Motors - YORI, Alfio (Archives of Acoustics, 2023)
Small boats, possessing outboard engines, are widely used in tourism and mammal watching within marine protected areas. Noise generated by this type of vessels has the capacity to negatively affect marine fauna, especially marine mammals, which use sound throughout all the phases of their lives. These tourism boats used in mammal watching may use different propulsion systems, such as gas, diesel or electric engines. To characterize underwater noise emitted by this type of vessels becomes relevant not only when assessing the acoustic impact produced by these different propulsion systems over the marine fauna living inside these protected marine areas, but also when determining which one produces the least impact. A comparative study of underwater noise emissions coming from small touristic boats was made in this study. Boats were similar in capacity and functions, although possessing different propulsion systems. Measurements were made on two boats with a 50 Hp internal combustion engine and one 5 Hp electric boat. These boats were selected to be studied because they have practically the same size, possess the same passenger-capacity and are used to make similar jobs and routes inside the protected area where they are operated. The electric boat showed a considerable decrease in underwater noise emissions, especially in low frequencies. This boat will produce a lower accumulated exposition of the fauna to the noise or will allow a closer approach to the observed species. Measurements were made between September 2018 and January 2020